The Cognitive Ecology of Stimulus Ambiguity: A Predator–Prey Perspective. (November 2019) - Leavell, Brian C.; Bernal, Ximena E.
Abstract : Organisms face the cognitive challenge of making decisions based on imperfect information. Predators and prey, in particular, are confronted with ambiguous stimuli when foraging and avoiding attacks. These challenges are accentuated by variation imposed by environmental, physiological, and cognitive factors. While the cognitive factors influencing perceived ambiguity are often assumed to be fixed, contemporary findings reveal that perceived ambiguity is instead the dynamic outcome of interactive cognitive processes. Here, we present a framework that integrates recent advances in neurophysiology and sensory ecology with a classic decision-making model, signal detection theory (SDT), to understand the cognitive mechanisms that shape perceived stimulus ambiguity in predators and prey. Since stimulus ambiguity is pervasive, the framework discussed here provides insights that extend into nonforaging contexts. Highlights: Advances in neurophysiology and sensory ecology are unraveling the mechanisms that shape an organism's perception of ambiguous stimuli. Sensory filters, neural noise, iterative sampling, attention, and integration of multiple stimulus components and modalities, and their interactions with state-dependent effects, collectively modify perceived stimulus ambiguity. Decisions made by predators (foraging) and prey (defense and escape) provide fertile ground to integrate recent advancements on the neural mechanism underlying decision-making. Placing these advances in an ecological context reveals that modifiers of stimulus ambiguity, both internal and external to an organism, interact dynamically to affect decision-making and can potentially alter ecological and evolutionary processes.